Polymerization of 10,16-Dihydroxyhexadecanoic Acid, Main Monomer of Tomato Cuticle, Using the Lewis Acidic Ionic Liquid Choline Chloride·2ZnCl2 - Gómez-Patiño, Mayra Beatriz; Gutiérrez-Salgado, Diana Yaremy; García-Hernández, Edgar; Mendez-Mendez, Juan Vicente; Andraca Adame, J. Alberto; Campos-Terán, José; Arrieta-Baez, Daniel (Frontiers in Materials, 2015)
10,16-dihydroxyhexadecanoic acid, main monomer of the tomato cuticle obtained from agro-residual wastes, was polymerized using (choline chloride.2ZnCl2) ionic liquid as catalyst at three different temperatures (80, 90 and 100 °C). The resulting polyesters obtained under these conditions were insoluble in most of the organic solvents and showed different physicochemical properties. While at 80 °C polymers were obtained as powder, at higher temperature they were found in viscous consistency. According with the CP MAS 13C NMR and FTIR-ATR analysis, polymers showed a linear structure with an increasing degree of esterification in position C-10. Polyesters were analyzed by means of differential scanning calorimetry (DSC), atomic force microscopy (AFM) and X ray diffraction (small- and wide-angle scattering, SWAXS) techniques.